Math, asked by kaisershazad60, 3 months ago

solve the following equation (5x-4)-(3x-1)=3​

Answers

Answered by ouk1122334455
1

Step-by-step explanation:

5x-4-3x-1=3

2x-3=3

2x=3+3

=2x=6

x=6/2

x=3

Answered by madeducators1
0

Given:

We have given an equation which is  (5x-4)-(3x-1)=3​

To FInd:

We have to simplify the equation for value of x.

Step-by-step explanation:

  • We have given the equation which is  (5x-4)-(3x-1)=3​
  • We will simplify the given with the rule of BODMAS in which this rule we will first of all simplify the brackets and then after that we will do the division and then followd by the  multiplication and then after of that addition and in the last subtraction.
  • In the given equation first of all we open the brackets and simplify them

        5x-4-3x+1=3

  • Now we take the all like terms together in the above equation

       5x-3x-4+1=3

  • Now we simplify the terms by adding them

        2x-3=3

  • Now we will simplify the above equation by taking -3 to the right hand side

      2x=3+3=6\\2x=6

  • Now for finding the value of x we will do the division

      x=\frac{6}{2} =3

Hence, the value of x is 3.

Similar questions